Com o terço entre os dedos: as marchas da Família com Deus pela Liberdade em Sergipe (1964) - Reis, Raphael Vladmir Costa (2019)
This dissertation consists of investigating the Marches of the Family with God for Freedom in Sergipe, used as a tool to legitimize the civil-military coup and carried out between April and May 1964, identifying their organizers, paths, participants, motivations and reactions caused in culture municipalities in which such events took place. To a large extent, it is considered appropriate to analyze the dynamics of the national / local political conjuncture, highlighting the modus operandi employed by the Catholic Church, female sectors and other social actors for the imagistic construction of anti-communism, ideological current that propelled the realization of those civic-ecclesiastical Therefore, in order to reach these objectives in the light of Cultural History, this work proposes to dialogue with concepts that make up the repertoire of this historiographical current re-signified by the third generation of the Annales, using also reports extracted in semi-structured interviews and trying to expand, thus, the understanding of conservatism in Sergipe.